Studi Kontribusi Workplace Spirituality terhadap Innovative Work Behavior - Nur Intan Rizkiah; Ali Mubarak (UNISBA Press, 2022)
Abstract. Work spirituality is a concept that related to aspects of spirituality to work and the work environment (Wulandari, F., 2014). Innovative work behavior is a work behavior that aims to generate, introduce and implement new things that are useful for the company (West & Farr in De Jong & Kemp, 2003). The purpose of this study was to determine the contribution of workplace spirituality and innovative work behavior in the creative division of Television and Radio Stations in Bandung City. The research method used is quantitative approach with multiple regression analysis. The measuring instrument used to measure workplace spirituality is a measuring tool developed by Ashmos & Duchon (2000), to measure innovative work behavior using the innovative Measuring of work behavior developed by De Jong & Den Hartog (2010). The results showed that workplace spirituality had a positive effect on innovative work behavior by 68.8%. Partially, the workplace spirituality factor that has the greatest influence on innovative work behavior is the inner life factor, while the factor that has the lowest influence is blocks to spirituality factor. Abstrak. Spiritualitas kerja merupakan sebuah konsep yang membahas keterkaitan aspek-aspek spiritualitas terhadap pekerjaan dan lingkungan kerja (Wulandari, F., 2014). Innovative work behavior adalah suatu perilaku kerja yang bertujuan untuk menghasilkan, memperkenalkan dan menerapkan hal-hal baru yang bermanfaat bagi perusahaan (West & Farr dalam De Jong & Kemp, 2003). Tujuan dari penelitian ini adalah untuk mengetahui kontribusi workplace spirituality dan innovative work behavior pada divisi kreatif Stasiun Televisi dan Radio di Kota Bandung. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan analisis regresi berganda. Alat ukur yang digunakan untuk mengukur workplace spirituality adalah alat ukur yang dikembangkan oleh Ashmos & Duchon (2000), untuk mengukur innovative work behavior menggunakan Measuring innovative work behaviour yang dikembangkan oleh De Jong & Den Hartog (2010). Hasil penelitian menunjukkan bahwa workplace spirituality berpengaruh positif terhadap innovative work behavior sebesar 68,8%. Secara parsial, faktor workplace spirituality yang memberikan pengaruh paling besar terhadap innovative work behavior adalah factor inner life, sedangkan faktor yang memberikan pengaruh paling rendah adalah factor blocks to spirituality.